Directors' liability a worldwide review - Loos, Alexander, 1950- (International Bar Association series ;, 2016)
"[This] comparative study of a crucial issue in corporate law gives practitioners a ... tool for ascertaining and comparing the law affecting directors liability in today s globalizing economies. Covering nearly fifty jurisdictions worldwide (including eight not previously covered), the third edition affords senior lawyers in major firms the opportunity to provide ... summaries on his or her home law on directors liability. Authors whose research appeared in earlier editions have updated their chapters, and the case law summarized and analysed now reflects published cases through the end of March 2016. The contributions describe the relevant law in force in each particular jurisdiction, along with an insightful discussion of trends and future prospects. For each of the different jurisdictions the authors detail and explain such factors as the following: national legal theories of director liabilities; recent cases dealing with directors liability; corporate governance; and indemnification and insurance. Where applicable, coverage also includes the legal implications of jurisdictional variations in such matters as judicial review, lawyer directorship, directors reliance on outside professionals, and the effect of the European Action Plan. References have been thoroughly updated throughout, and include many new online sources."--